Synthesis and Biological Activity Study of Co and Cr Complexes with α-(2-Salsayl)-N-phenyl Nitrone and Oxide Nanoparticles - Dhamiaa Abdul-Shaheed Issa; Hayder Baqer Abdullah; Faeza Abdulkareem Al-Mashal (Indonesian Journal of Chemistry, 2023)
This paper describes the synthesis of two complexes from the ligand α-(2-Salsayl)-N-phenyl nitrone with CoCl2 and CrCl2. The ligand was characterized by several spectroscopic techniques (ultraviolet/visible (UV/Vis), nuclear magnetic resonance (1H-NMR and 13C-NMR), Fourier-transform infrared spectroscopy (FTIR), and mass spectrometry (MS). While infrared, ultraviolet-visible (UV-Vis), thermal analysis, and job method studies were used to reveal the structure of the complexes. The synthesized complexes were then synthesized by the sonochemical method, and the copper and chromium oxide nanoparticles were produced using the thermal decomposition method. Scanning electron microscopy (SEM), Energy dispersive X-ray spectroscopy (EDX), and X-ray diffraction (XRD) characterization confirmed the formation of Co3O4 and Cr2O3 nanoparticles. Antimicrobial studies of the complexes against some microorganisms, such as Staphylococcus epidermis and Escherichia coli, utilizing the disk diffusion method, revealed the antibacterial activity of the complexes.